2018
DOI: 10.3390/life8020013
|View full text |Cite
|
Sign up to set email alerts
|

Caveats to Exogenous Organic Delivery from Ablation, Dilution, and Thermal Degradation

Abstract: A hypothesis in prebiotic chemistry argues that organics were delivered to the early Earth in abundance by meteoritic sources. This study tests that hypothesis by measuring how the transfer of organic matter to the surface of Earth is affected by energy-dissipation processes such as ablation and airbursts. Exogenous delivery has been relied upon as a source of primordial material, but it must stand to reason that other avenues (i.e., hydrothermal vents, electric discharge) played a bigger role in the formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…not sufficiently large to protect gases from escaping the mineral matrix (Sears 1975;Shingledecker 2014;Mehta et al 2018). Additionally, it could be possible that the Aguas Zarcas meteorite chip we obtained for this work was from a more degassed portion of the Aguas Zarcas parent body.…”
Section: Abundance and Molecular Distribution Of Carbonyl Compoundsmentioning
confidence: 99%
“…not sufficiently large to protect gases from escaping the mineral matrix (Sears 1975;Shingledecker 2014;Mehta et al 2018). Additionally, it could be possible that the Aguas Zarcas meteorite chip we obtained for this work was from a more degassed portion of the Aguas Zarcas parent body.…”
Section: Abundance and Molecular Distribution Of Carbonyl Compoundsmentioning
confidence: 99%
“…The infall of carbonaceous meteorites and their associated organic compounds could have also contributed prebiotic compounds to the early oceans. But the survival of extraterrestrial organic molecules, mainly in the form of interplanetary dust particles (IDPs), during atmospheric passage and heating is a major concern [10,11]. As was the case with prebiotic compounds made directly on Earth, oceanic extraterrestrial compounds accumulation could have been limited by hydrothermal circulation if it existed.…”
Section: Introductionmentioning
confidence: 99%
“…Atmospheric entry of bolides, however, can have deleterious effects on bolide size and composition. Hills and Goda (1993) demonstrated that large objects ablate as they decelerate through the atmosphere, and Mehta et al (2018) reported that *60 to >99% of the object's mass could be lost to ablation. Even so, because comets dissipate energy at high altitude, the blast wave is weaker (Hills and Goda, 1993), which may allow for the survival of organics.…”
Section: Discussionmentioning
confidence: 99%